Optimalisasi Pemantauan Kesehatan Balita Stunting melalui Buku Monitoring Gizi Anak di Kabupaten Rote Ndao, NTT - Ari Indra Susanti; Siti Nur Fatimah; Atriany Nilam Sari; Dani Ferdian; Yusrima Syamsina Wardani; Noormarina Indraswari; Didah Didah; Wiyoko Yudhantara; Yulika Yulika; Yogi Lasril (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Rote Ndao Regency, which is located on one of the outer islands in NTT Province, has a total stunting prevalence of 23.48%. The improvement of stunting with interventions in the health and non-health sectors has a considerable contribution. This activity aims to carry out a stunting control improvement program by utilizing child nutrition monitoring books as a medium in monitoring the health of stunting toddlers in Rote Ndao Regency. The target in this activity is families who have toddlers aged 13-48 months as many as 88 children. The method of this activity is that all targets are given a monitoring book and supplementary feeding and Zinc supplementation is carried out for 12 weeks. The results showed that the provision of additional feeding assistance and supplementation improved nutritional status with increased weight and even this activity increased the motivation of the family to improve the child's lifestyle and health status.